ANALISIS KESIAPSIAGAAN SAFETY DRIVING PADA PENGEMUDI MOBIL PRIBADI DI RUTE TOL CIPALI (CIKOPO – PALIMANAN) - Nadya Eka Febrina; Bina Kurniawan; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Safety driving is part of the road safety culture to see how safety a person in the act of driving. There are three factors that influence human behavior in driving, the host factor (driver), agent factors (physical energy motor vehicles), and environmental factors. The main factors that causing an accident while driving is a factor undisciplined driving behavior that is equal to 80-90%. The drivers behavior who are not ready to implement a safety driving course will cause an accident on the highway. One of the most frequent accident in highway route is a Cipali highway which have quite different characteristics than the other, due the highway route is one of the longest highway route in Indonesia. The purpose of this research is to analyze the safety driving preparedness to the personal drivers in Cipali hihway route. This research is using descriptive qualitative method. The data collected by indepth interview and observation to 8 informant (5 driver, one ambulance employees, one employee highway patrol, and the first Head of the Traffic PT. LMS). The results of this research showed that safety driving preparedness to the personal drivers in Cipali highway route is less because they assume that driving safely make driving time becomes longer. It can be concluded in this research that the human factor (road user) is fairly bad, and to be expected the driver always ready to implement safety driving.